Concurrent hand-foot skin reaction and hair depigmentation with sunitinib: Report of a case and literature review of kinase inhibitors and blocking antibodies - Shuchi Bansal; Kabir Sardana; Kishore Singh; Vijay K Garg (Wolters Kluwer Medknow Publications, 2014)
Kinase inhibitors have revolutionized cancer therapy by becoming the first-line agents for advanced solid malignancies replacing the traditional chemotherapeutic agents. Cutaneous side-effects with these drugs are common, but owing to their infrequent use in Indian patients, our current knowledge of toxicity is scanty and primarily based on the western literature. Cutaneous reactions can adversely affect patients' quality of life (QoL) and can lead to dose modifications and treatment interruptions. The report discusses concurrent hand-foot skin reaction (HFSR) and hair depigmentation in an Indian patient being treated with sunitinib for advanced renal cell carcinoma. The pathogenesis and treatment strategies for this characteristic phenomenon and other cutaneous toxicities of kinase inhibitors have also been reviewed.